OUTDOOR EDUCATION: A CONTEXTUAL ENGLISH LEARNING ACTIVITY TO IMPROVE WRITING ABILITY OF YOUNG ADOLESCENTS (A CLASSROOM ACTION RESEARCH) - Sri Setyarini (Universitas Sebelas Maret, 2017)
This study describes an implementation of Outdoor Education as a contextual learning activity to improve writing ability of young adolescents. It aims at (1) investigating how Outdoor Education is implemented in teaching English to young adolescents to improve their writing ability; (2) identifying the challenges faced by the teacher in the implementation of this learning activity; (3) finding the strategies to overcome the challenges faced by the teacher. A Classroom Action Research was employed as a research design which was divided into four phases namely Planning, Acting, Observing, and Reflecting. Moreover, data were collected through several instruments, namely observation, students’ writings (documentation), and interview with the students. The collected data in the form of students’ writing were analyzed by using the scoring rubric suggested by Brown (2007) and referred to qualitative data analysis proposed by Hamied and Malik (2016). The result of the study revealed that Outdoor Education has successfully improved students’ writing ability because the students may understand the content of the lesson and new vocabulary contextually. In addition, the improvement found because the students enjoyed and were excited in their learning in suchan informal and interesting context (Berns&Errickson, 2001). Comparing the result of Pre-writing and Second Cycle Writing may reveal the better students’ writing ability (from 56.16 to 80.17). However, the teacher found some challenges to implement it since the adolescents seemed to spend the time inefficiently thus to deal with those the teacher provided clear briefings before doing the activity and asked them to open the dictionary if they got difficult words in writing their descriptive text.